2019
DOI: 10.1038/s41405-019-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Demirjian’s method for dental age estimation in a group of Egyptian children

Abstract: AimsThe aims of this study were to evaluate the applicability of Demirjian’s method for dental age assessment in a group of Egyptian children in Minia city and to develop an age predictive equation suitable for the studied group.Subjects and methodsIn this retrospective, blind, cross-sectional study, 160 dental panoramic radiographs (DPTs) were selected from 420 DPTs from healthy children aged between three and 10 years old from the archived medical files of patients attending Minia University Dental Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Moness Ali et al performed regression analysis using Demirjian’s staging method in Egyptian children between 3 and 10 years. They could prove that precising the Demirjian staging method in a population could lead to a more accurate dental age estimation, which leads to a better approach to chronological age [ 33 ]. In the clinical application of dental age determination, the legal age limits are relevant for social benefits, penalties and obligation to care for minors vs. adults.…”
Section: Discussionmentioning
confidence: 99%
“…Moness Ali et al performed regression analysis using Demirjian’s staging method in Egyptian children between 3 and 10 years. They could prove that precising the Demirjian staging method in a population could lead to a more accurate dental age estimation, which leads to a better approach to chronological age [ 33 ]. In the clinical application of dental age determination, the legal age limits are relevant for social benefits, penalties and obligation to care for minors vs. adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that DM was very much influenced by ethnicity and sex (Yan et al, 2013; Jayaraman et al, 2013; Carneiro et al, 2015; Moness Ali et al, 2019). Willems et al (2001) offered a revised DM.…”
Section: Introductionmentioning
confidence: 99%
“…As in this study, a common result of Demirjian method has been overestimated age. [21][22][23][24][25] This difference may have been caused by the fact that the data of an age determination method applied on the French-Canadian ethnicity 18 were used to determine data for different societies and geographies. To more accurately estimate the dental maturity of different groups, population-specific standards or modifications should be constructed.…”
Section: Discussionmentioning
confidence: 99%